Proces doskonalenia jakości produktu - system bardziej skutecznego zaspokojenia potrzeb i oczekiwań klienta w przedsiębiorstwach agrobiznesowych - Pawłowska, Bożena (Product Quality Improvement Process - a More Efficient System of Customer's Needs and Expectations Satisfaction in Agribusiness Enterprises, 2005)
This article presents own research findings and refers to the problem of level involvement in product quality improvement processes of agribusiness enterprises in order to create a more customer orientation system to illustrate the activities needed to improve customer satisfaction of purchased products.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 169-175